$$\exp \left(\lim_{s\to 1} \, \zeta (s) \sum _{k=1}^{1 n} \frac{1-\text{If}[k \bmod n=0,n,0]}{k^{s-1}}\right) = \text{If}\left[n=0,1,\frac{n^{1 n}}{\frac{(1 n)!}{1^n}}\right]$$
$$\exp \left(\lim_{s\to 1} \, \zeta (s) \sum _{k=1}^{2 n} \frac{1-\text{If}[k \bmod n=0,n,0]}{k^{s-1}}\right) = \text{If}\left[n=0,1,\frac{n^{2 n}}{\frac{(2 n)!}{(1\ 2)^n}}\right]$$
$$\exp \left(\lim_{s\to 1} \, \zeta (s) \sum _{k=1}^{3 n} \frac{1-\text{If}[k \bmod n=0,n,0]}{k^{s-1}}\right) = \text{If}\left[n=0,1,\frac{n^{3 n}}{\frac{(3 n)!}{(2\ 3)^n}}\right]$$